Exploring the Impact of Cultural Beliefs and Practices on Women's Education in Northern Nigeria - Temitope Yewande; Ayokunumi Olawunmi (Journal of Education Review Provision, 2023)
This qualitative research looks at how societal norms and practices in Northern Nigeria have affected women's access to and participation in higher learning. This research delves into the lived experiences and viewpoints of women who have been unable to further their education due to cultural factors through in-depth interviews and focus groups. The research shows that societal norms are a driving force behind gender inequality and the suppression of women's education opportunities. Key factors recognized as contributing to these obstacles include poverty, gender segregation, and traditional gender roles and expectations. The research also notes that patriarchy and the underrepresentation of women in power structures are major factors in discrimination against women. Several policy and practice suggestions are made based on the findings of the study, such as the need to promote gender-sensitive policies and practices, address economic barriers, challenge gender stereotypes and expectations, and encourage women to take on positions of leadership and participate in decision-making.